Carburizing of Rolled and Non-Rolled High Manganese Steel - Ezzatie Ismadi, Amalina; Irwan Yahaya, Mohamad; Mohamed Noor, Rizal; Mahadzir Mohammud Mahmood, Mohd; Rahman Hemdi, Abdul; ., . (International Journal of Engineering and Technology, 2018)
High manganese steel is a steel type with manganese content of 15 – 30 %. It is applied to various industries based on various properties inclusive of high strength ability. Problems or defects occur during the deformation of this steel include tearing and cracking. High loads applied during the deformation process lead to the increase the problems and damages of the machine components. In order to resolve this, carburizing was introduced. Carbon diffused into the steel surface changes the strength and microstructure. The research is carried out to reduce the load and defect of the product and machine component along the deformation process. In this paper, an experimental work was undertaken to compare the results of tensile test of pack carburizing (non-rolled) and gas carburizing (rolled). The objective of this work is to investigate the effect of carburizing on the strength-ductility properties of rolled and non-rolled Fe-24Mn steel. Investigation of the stress – strain relationships of three specimens for rolled and non-rolled with different carburizing time is the aim of this paper. For the purpose of achieving this aim, the measurements and evaluation of yield strength, ultimate tensile strength, elongation and hardness were performed on the steel samples subjected to tensile loading. The finding witnesses that the carbon improves the mechanical properties of this steel. The most commonly accepted method in evaluation of the mechanical properties of material would be the tensile test. This test explains the different results of stress-strain relationship with and without rolling processes with different carburizing time. Finally, this research indicates some future investigations required in order to support the quality of the findings.